LAW ENFORCEMENT AGAINST FOOD HOARDING ACTIVITIES DURING THE COVID-19 - Dwi Desi Yayi Tarina; Muthia Sakti; Dinda Dinanti (UNTAG Law Review, 2021)
The world is currently facing the same problem, namely the coronavirus or Covid 19. During this pandemic, all sectors of the economy are very influential on survival.  The existence of Large-Scale Social Restrictions (PSBB) has caused people to panic buying. So, in other words, there has been a new problem, carrying out the activities of hoarding staple food carried out by entrepreneurs, suppliers, and traders. The hoarding results in losses to the community or business actors. By conducting juridical normative research methods based on applicable laws and regulations, law enforcement is needed to realize justice, certainty, and benefits. The policy in tackling the crime of food hoarding in Indonesia has been regulated in Law Number 18 of 2012 concerning Food and Law Number 7 of 2014 concerning Food. Moreover, it has also regulated in Government Regulation No. 17 the Year 2015 on Food Security and Nutrition, which regulates the mechanism, procedure, the maximum amount of staple food storage by businesses. Business actors who deliberately hoard food may be sentenced to imprisonment for a maximum of 7 (seven) years or a maximum fine of Rp. 100,000,000,000.00 (one hundred billion rupiah). It can be concluded that criminal law policy-related efforts to combat the crime of hoarding of food have been regulated in the Law of Food and Trade Act.